Pop-Up Book Digital sebagai Solusi Inovatif untuk Edukasi Seksual Guru Sekolah Dasar - Rinawati, Rinawati; Soimah, Soimah; Fandi, Fandi (Journal of Community Development and Empowerment, 2025)
Sexual education is a fundamental aspect of learning in elementary schools to equip students with a proper understanding of reproductive health, physical changes, as well as the concepts of personal boundaries and protection against sexual violence. However, in practice, many teachers face challenges in delivering this material effectively due to a lack of understanding, limited learning resources, and social stigma surrounding the topic. Therefore, innovation in learning media is needed to help teachers comprehend and teach sexual education more interactively and systematically. This study aims to explore the use of Digital Pop-Up Books as an innovative solution to enhance elementary school teachers' understanding of sexual education. The research method employed is a qualitative approach, utilizing literature studies and limited trials with a number of elementary school teachers. The research findings indicate that Digital Pop-Up Books provide a more engaging learning experience and facilitate teachers in understanding and delivering sexual education material. This medium integrates visual and interactive elements, which not only improve teachers' conceptual understanding but also aid in conveying the material more effectively and in accordance with students' cognitive development levels. By utilizing digital technology, Digital Pop-Up Books can serve as a flexible, easily accessible learning medium that can be adapted to the needs of teachers and the characteristics of students. This study recommends further development of Digital Pop-Up Book content to ensure greater relevance to the educational curriculum and support effective learning in elementary schools. Thus, this innovation has the potential to be an effective solution in addressing the challenges faced by teachers in teaching comprehensive sexual education in a culturally appropriate manner in Indonesia.